Incidence and predictors of mortality in children with diabetic ketoacidosis in the comprehensive specialized referral hospitals of West Amhara Region, Northwest Ethiopia: a retrospective follow-up study - Shimelash, Rahel Asres; Belay, Getaneh Mulualem; Aknaw, Worknesh; Shibabaw, Aster Tadesse; Adebabay, Aderajew Agmas; Gedefaw, Gezahagn Demsu; Kassie, Tadele Derbew; Zemariam, Alemu Birara (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background Diabetic ketoacidosis is one of the major life-threatening conditions associated with acute metabolic complications. It remains a major public health problem in developing countries such as Ethiopia. Objective To assess the incidence and prediction of mortality in children with diabetic ketoacidosis in West Amhara Region Comprehensive Specialized Referral Hospitals, Northwest Ethiopia, in 2022. Methods An institution-based retrospective follow-up study was conducted among 423 study participants with a confirmed diagnosis of diabetic ketoacidosis from 01/01/2017 to 31/12/2021. Data were entered, coded, cleaned, and checked using Epi-Data version 4.6 and exported to Stata version 14 for data analysis. Results A total of 401 child records were included in the final analysis and were followed for 3781 days during the study period. The overall mortality of children with diabetic ketoacidosis was 10.6 per 1000 person-days observed (95% CI: 7.8-14.4) during the entire follow-up period. Hypoglycemia (AHR=4.6; 95% CI: 2.13-10.1), rural residence (AHR=2.9; 95% CI=1.01-8.11), age younger than five (AHR=4.4; 95% CI=1.4-13.7) or between five and 10 (AHR=3.1; 95% CI=1.1-8.8), and female gender (AHR=2.6; 95% CI=1.1-5.8) were significant predictors of mortality. Conclusions The incidence rate of mortality in children with diabetic ketoacidosis was relatively high. Age, rural residence, female gender, and hypoglycemia were significantly predictive of mortality. Community education or mass campaigns about the signs and symptoms of diabetic ketoacidosis may reduce the mortality rate in children.